Flua - Guerra, Silvia Gabriela Raimundo [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
O trabalho apresenta um dos estados da saúde mental, o definhamento, através de um Motion Graphics informativo. Este projeto foi desenvolvido trabalhando com a teoria do Motion Graphics em conjunto com diretrizes do design da informação e do design emocional.

The work presents one of the states of mental health, the languishing, through an informative Motion Graphics. This project was developed working with motion graphics theory in conjunction with information design and emotional design guidelines.
Flow
Keywords: Saude mental; Pandemias; Emoções; Mental health; Motion; Pandemics; Design